MITIGASI PERMASALAHAN RUMAH NEGARA DALAM MEWUJUDKAN PENGELOLAAN BARANG MILIK NEGARA YANG EFEKTIF DAN AKUNTABEL - Taswin Taswin; Arywarti Marganingsih, Siti Kholiyah, Enggar Giri Pambudi (CV. Adiba Aisha Amira, 2025)
Provisions for the management of state houses are regulated by laws and regulations, ranging from laws and regulations to ministerial regulations. However, in the implementation of state houses management, there are still issues that do not comply with these provisions, including physical, administrative, and legal issues. The method or approach used is a scientific study of these issues using a statutory regulatory approach. Efforts to mitigate these issues to support the realization of orderly physical, administrative, legal, targeted, and accountable state houses management can be carried out by strengthening the legal basis through the development of internal regulations, increasing legal awareness among stakeholders, law enforcement, increased supervision and control of state assets for retired or transferred employees, and enhanced coordination with relevant ministries.